studi perencanaan pembangkit listrik tenaga mikrohidro (PLTMH) desa tawa kecamatan gane barat selatan kabupaten halmahera selatan - Muhammad Yunus H Abbas; Ahmad P Sardju (Fakultas Teknik Universitas Khairun, 2021)
The problem of the need for electrical energy, especially petroleum as a source of energy is decreasing, so that savings must be anticipated as early as possible. One of the saving measures taken to reduce the use of petroleum in order to meet electricity needs is to use water energy as renewable energy, so in this study PLTMH is planned. The things that are taken into account in planning PLTMH are conduits, water tanks, rapid pipes, powerhouses, turbines and generators. The PLTMH research was conducted in Tawa Village, Gane Barat Selatan District, South Halmahera Regency. The results obtained are a water discharge of 0.28 m3 / s and a waterfall height of 12 meters, a diameter of 12 cm of rapid pipe, a length of 19.20 m of rapid pipe. kW, and the generator is sporadically coupled so that the net power of the turbine is equal to the gross power of the generator. The efficiency of the generator is 90%, so that it produces a rise power of 18.88 kW divided by cos φ which is equal to 23.6 kVA